146k views
1 vote
Find the missing coefficient. (5d − 7)(5d − 6) = 25d2 ++ 42 5 65 –5 –65

User Cong Wang
by
5.4k points

2 Answers

3 votes
i do believe it is -65d because the equation will look like this in the end
-65d=-65d.
User Suborx
by
6.0k points
7 votes

Answer:

-65d

Explanation:

(5d − 7)(5d − 6)


(5d - 7)(5d - 6)

Multiply it using FOIL method to find the missing term

Multiply 5d inside the second parenthesis and then multiply -7 inside second parenthesis


5d \cdot 5d= 25d^2


5d \cdot -6= -30d^2


-7 \cdot 5d=-35d


-7 \cdot -6=42

Now write all the terms together


25d^2-30d-35d+42

Combine like terms


25d^2-65d+42

HEre -65d is missing

User Ashish Sarkar
by
6.8k points